2016
DOI: 10.1111/xen.12261
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of B‐cell activation and antibody production by triggering inhibitory signals via the PD‐1/PD‐ligand pathway

Abstract: Enhancing inhibitory signals may be part of future protocols to better control humoral immunity to allo- and xenografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Preferential PD-1 expression on differentiated and activated B cells in blood and CSF. Programmed death-1 (PD-1) is a surface regulatory "check point" molecule identified prominently on T follicular helper cells and, less frequently, on B cells, NK cells, NKT cells, and other myeloid-derived cells (18). PD-1 was expressed on a minority of circulating B cells but significantly more commonly on B cells in the CSF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Preferential PD-1 expression on differentiated and activated B cells in blood and CSF. Programmed death-1 (PD-1) is a surface regulatory "check point" molecule identified prominently on T follicular helper cells and, less frequently, on B cells, NK cells, NKT cells, and other myeloid-derived cells (18). PD-1 was expressed on a minority of circulating B cells but significantly more commonly on B cells in the CSF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PD‐1 is thought to be involved in the induction of anergy and exhaustion in CD8 + T cells . Furthermore, we and others have shown that PD‐L1‐mediated triggering of PD‐1 on B cells decreases activation and antibody production . The diversity of cell types and functions that are modulated by PD‐1/PD‐L1 is in line with the view of this receptor‐ligand pair as important regulator of immune checkpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the physiological role of PD‐1/PD‐L1 and the observations in allotransplantation, transgenic expression of human PD‐L1 on porcine cells is promising to protect porcine tissue from human immune responses. As proof‐of‐principle, we and others have shown that porcine cells over‐expressing human PD‐L1 are indeed weak stimulators of immune responses in vitro and also in a pig‐to‐rat cell transplantation model in vivo . The usefulness of this concept has not yet been investigated in transgenic pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The resurgence of xenotransplantation is now obvious [9,10,106], with prolonged survival of cellular and solid organ xenografts (Figure 2) associated with the administration of newer costimulation blockade agents [107,108] and access to genetically-engineered pigs. Our increasing knowledge of the pig genome [109] will almost certainly lead to further genetic manipulations.…”
Section: Resultsmentioning
confidence: 99%